(untitled) (MODERN CONSTRUCTION AND ARCHITECTURE, 2023)
The formation of urban space that is comfortable and safe for its users is the highest goal of modern urban planning science. After analysing existing planning practices, it was found that the primary prerequisite for the formation of urban space is to determine the needs of the area, which are established after comprehensive analyses and assessment of the territories. The needs determine the direction of their development. This paper reviews the existing methods of analysis and assessment of territories and identifies their characteristic features that require analysis and assessment to establish clearer actions to improve the space. This article investigates the issue of comprehensive analysis and assessment of urban areas and their impact on the formation, reform and reconstruction of urban space. The purpose of this study was to systematize knowledge on the analysis and assessment of urban areas. Based on the identified problems, the prerequisites for the formation of a comfortable urban space for all levels of needs of its residents and users are established. In a modern city, many processes take place simultaneously, which affect the functional division of territories in accordance with the dominant activities on them. Formulating clear urban planning tasks helps to: preserve the positive and change the negative characteristics of urban space, take into account the views of local residents and space users, analyse investment opportunities, primarily to understand the material prospects of the area. A comprehensive analysis and assessment of the city’s territories allows identifying problems or conflict situations in the urban space that negatively affect its functioning, development and comfort. Usually, the definition of city comfort is defined as a separate assessment criterion, but in the author’s opinion, it is the formation of a comfortable urban space that is the main task for urbanists, which includes many criteria that ensure the safety, environmental friendliness, identity and modernity of the space in accordance with the needs of the local community. As a result of the research, it was found that supplementing the existing practices and methods of analyzing and assessing urban space in accordance with the current needs of urban planning would allow for a better and more relevant formation of the urban space that is needed by the resident and its user.